STRATEGIES IN TEACHING READING COMPREHENSION: LISTEN-READ-DISCUSS AND CONTEXTUAL REDEFINITION IN INSTRUCTING READING UNDERSTANDING - Lilih Insyirah; Murni Mahmud; Munir Munir; Muh Tahir (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
This study compared the effectiveness of the Contextual Redefinition Strategy (CRS) and the Listen-Read-Discuss (LRD) strategy in improving students’ reading comprehension of narrative texts. Conducted at SMKN 2 Selayar with X TKJ as experimental class 1 (CRS) and X TKR as experimental class 2 (LRD), the research employed quantitative analysis using paired and independent sample t-tests with SPSS 23. The results showed a significant difference in reading comprehension between the two groups, with CRS demonstrating greater effectiveness (Sig. = 0.000 < 0.05). CRS supported vocabulary acquisition and encouraged contextual prediction, leading to deeper understanding. In contrast, while LRD promoted active participation, it lacked explicit vocabulary instruction, which may have limited its impact. These findings align with prior studies, confirming that CRS is more effective in enhancing reading comprehension, particularly due to its focus on vocabulary development and contextual learning.